Britain, de??tente, and the Helsinki CSCE : 'Fathers of the Final Act' - Hebel, Kai (Cold War history series., 2026)
This book offers the first in-depth account of the United Kingdom's contribution to the rapprochement between East and West that culminated in the successful negotiation of the Helsinki Final Act of 1975.Britain's role in this historic achievement has been understudied and understated. This book rectifies this shortcoming by tracing London's important contribution to East-West diplomacy with a special focus on the negotiations of the Helsinki Final Act (1972-75). The Final Act was the product of almost three years of intense bargaining in the context of the Conference on Security and Cooperation in Europe. Along with 34 other states, the UK negotiated core aspects of European international relations, including the political, territorial, and normative order of the divided continent. Taking full advantage of its new role as a member of the European Community and its traditional part in NATO, British negotiators skillfully navigated the opportunities and pitfalls of multilateral diplomacy. Their success in hammering out several of the most contested and most innovative provisions of the Helsinki Accord earned them the moniker of 'Fathers of the Final Act'. Based on extensive archival research in eleven countries on three continents, this book traces the evolution of the negotiations, providing a compelling bottom-up account of how diplomacy works in practice against the backdrop of inter-state conflict and unequal power.This book will be of much interest to students of Cold War History, European history, British history, and International Relations.